Osteocalcin and GPR158: linking bone and brain function - Li, Jingjing; Lou, Shujie; Bian, Xuepeng (Frontiers in Cell and Developmental Biology, 2025)
Osteocalcin (OCN), a small protein secreted by osteoblasts, has attracted significant attention for its role as an endocrine factor in regulating the central nervous system (CNS) via the bone-brain axis. As a critical receptor for OCN, G protein-coupled receptor 158 (GPR158) facilitates the proliferation, differentiation, and survival of neural cells while directly influencing neurons' structural and functional plasticity, thereby modulating cognitive function. Additionally, GPR158 is involved in cellular energy metabolism and interacts with proteins such as regulators of G protein signaling 7 (RGS7), broadening the understanding of OCN’s impact on neural activity. Notably, GPR158 displays region- and cell type-specific bidirectional effects under certain pathological conditions, such as tumor development and mood regulation, adding complexity to its mechanisms of action. Although the precise biological mechanisms underlying the OCN/GPR158 signaling pathway remain incompletely understood, its association with neurodegenerative diseases (NDs), including Alzheimer’s disease (AD) and Parkinson’s disease (PD), is becoming increasingly evident. Thus, a systematic summary of OCN/GPR158 in CNS regulation and NDs will deepen understanding of its role in brain function and support the development of new therapeutic targets and strategies.